A regression model of stream water quality based on interactions between landscape composition and riparian buffer width in small catchments - Pissarra, Teresa Cristina Tarlé [UNESP]; Valera, Carlos Alberto [UNESP]; Costa, Renata Cristina Araújo [UNESP]; Siqueira, Hygor Evangelista [UNESP]; Filho, Marcílio Vieira Martins [UNESP]; do Valle Júnior, Renato Farias [UNESP]; Fernandes, Luís Filipe Sanches [UNESP]; Pacheco, Fernando António Leal [UNESP] (MDPI, 2019)
Riparian vegetation represents a protective barrier between human activities installed in catchments and capable of generating and exporting large amounts of contaminants, and stream water that is expected to keep quality overtime. This study explored the combined effect of landscape composition and buffer strip width (L) on stream water quality. The landscape composition was assessed by the forest (F) to agriculture (A) ratio (F/A), and the water quality by an index (IWQ) expressed as a function of physico-chemical parameters. The combined effect (F/A × L) was quantified by a multiple regression model with an interaction term. The study was carried out in eight catchments of Uberaba River Basin Environmental Protection Area, located in the state of Minas Gerais, Brazil, and characterized by very different F/A and L values. The results related to improved water quality (larger IWQ values) with increasing values of F/A and L, which were not surprising given the abundant similar reports widespread in the scientific literature. But the effect of F/A × L on IWQ was enlightening. The interaction between F/A and L reduced the range of L values required to sustain IWQ at a fair level by some 40%, which is remarkable. The interaction was related to the spatial distribution of infiltration capacity within the studied catchments. The high F/A catchments should comprise a larger number of infiltration patches, allowing a dominance of subsurface flow widespread within the soil layer, a condition that improves the probability of soil water to cross and interact with a buffer strip before reaching the stream. Conversely, the low F/A catchments are prone to the generation of an overland flow network, because the absence of permanent vegetation substantially reduces the number of infiltration patches. The overland flow network channelizes runoff and conveys the surface water into specific confluence points within the stream, reducing or even hampering an interaction with a buffer strip. Notwithstanding the interaction, the calculated L ranges (45-175 m) are much larger than the maximum width imposed by the Brazilian Forest Code (30 m), a result that deserves reflection.
Keywords: Brazilian Forest Code; Interaction term; Landscape composition; Regression model; Riparian buffer width; Water pollution